Identification, classification and assessment of dyskinesia in children with cerebral palsy: A survey of clinicians. (31st October 2017) - Stewart, Kirsty; Tavender, Emma; Rice, James; Harvey, Adrienne
Abstract : Aim: The aims of this study were to investigate clinicians' knowledge, and barriers they perceive exist, relating to the identification and measurement of dyskinesia (dystonia/choreoathetosis) in children with cerebral palsy (CP) and to explore educational needs regarding improving identification and assessment of dyskinesia. Methods: This was a cross‐sectional online survey of clinicians working with children with CP. Data analysis was descriptive, with qualitative analysis of unstructured questions. Results: In total, 163 completed surveys from Australian clinicians were analysed. Respondents were allied health ( n = 140) followed by medical doctors ( n = 18) working mainly in tertiary hospitals and not‐for‐profit organisations. Hypertonia subtypes and movement disorders seen in children with CP appear to be identified by clinicians, although limited knowledge about dyskinesia and access to training were reported as significant barriers to accurate identification. Despite knowledge of available measurement scales, only a small percentage were used clinically and reported to be only somewhat useful or not useful at all. Barriers identified for use of scales included limited training opportunities and knowledge of scales and lack of confidence in their use. Conclusion: A lack of confidence in identifying and measuring movement disorders in children with CP was reported by Australian clinicians. It was identified that a greater understanding of dyskinetic CP and the tools available to identify and measure it would be valuable in clinical practice. The results of this survey will inform the development of a 'Toolbox' to help identify, classify and measure dyskinetic CP and its impact on activity and participation using the framework of the International Classification of Functioning, Disability and Health.